Tom Clancy under fire [compact disc, unabridged] - Blackwood, Grant (Clancy, Tom, 1947-2013. Jack Ryan, Jr., 2015)
On a routine intelligence gathering mission in Tehran, Jack Ryan, Jr., has lunch with his oldest friend, Seth Gregory, an engineer overseeing a transcontinental railway project. As they part, Seth slips Jack a key, along with a perplexing message.